Evaluation of Sexual Function in Women with Rheumatoid Arthritis - Coskun, Burhan; Coskun, Belkis Nihan; Atis, Gokhan; Ergenekon, Erbil; Dilek, Kamil (Urology Journal, 2014)
Abstract PURPOSE: To evaluate the link between rheumatoid arthritis (RA) and female sexual functioning. Material and Methods: A total of 32 women with RA and 20 healthy age matched controls were enrolled in this study. The participations are asked to complete Female Sexual Function Index (FSFI), The Short form 36 (SF-36) Health Survey and Beck Depression Inventory (BDI) questionnaires. Results: The groups were comparable in terms of demographic characteristics. The women with RA represented significantly worse sexual functioning in category of desire, arousal, lubrication, orgasm, satisfaction domain and total FSFI score compared with healthy women (P = .0001, P = .0001, P = .0001, P = .0001, P = .022 and P = .0001, respectively). The mean BDI scores for the patients with RA were greater than control group (P = .036). Women with R Aalso had significantly lower quality of life (QoL) parameters: physical functioning, limitations due to physical health, pain, general health, vitality and limitations due to emotional problems compared with healthy women (P = .0001, P = .0001, P = .028, P = .002, P = .001 and P =.0001, respectively). Conclusion: The present study shows that a significant percent of patients with RA had sexual dysfunction and also deterioration in QoL.